Kembalinya Tradisi: Rasionalitas dan Etika Komunitarian Alasdair MacIntyre - Amin Mudzakkir (Societas Dei: Jurnal Agama dan Masyarakat, 2017)
ABSTRACT: This paper will discuss rationality and ethics in the thought of Alasdair MacIntyre. Like other communitarian thinkers, tradition is the key word in his thinking. MacIntyre's rationality and ethics are tradition-based rationality and ethics. The return of tradition in the debate of rationality and ethics is a critique of the Enlightenment project which assumes that tradition is irrational. But MacIntyre also disagrees with the post-enlightenment argument with a relativist and perspective tendency. However the rationality and ethics proposed by MacIntyre still has a certain principle of objectivity. Used in contemporary realities, including in Indonesia, Alasdair Macintyre's thought is useful for understanding political identity critically. KEYWORDS: rationality, ethics, traditions, communiatrian, Alasdair MacintyreÂ